2021
DOI: 10.1017/bpp.2021.34
|View full text |Cite
|
Sign up to set email alerts
|

Motivated reasoning, fast and slow

Abstract: Are people more likely to (mis)interpret information so that it aligns with their ideological identity when relying on feelings compared to when engaging in analytical thinking? Or is it the other way around: Does deliberation increase the propensity to (mis)interpret information to confirm existing political views? In a behavioral experiment, participants (n = 1207, Swedish sample) assessed numerical information concerning the effects of gender quotas and immigration either under time pressure or under no tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…This experiment revealed that deliberation did not increase political polarization (i.e., disagreement between Democrats and Republicans, Bago et al, 2020; for further evidence indicating that deliberation manipulations do not increase motivated reasoning, see Strömbäck et al, 2021). Instead, deliberation increased overall accuracy (i.e., agreement with pro-climate change arguments) (Bago et al, 2020b).…”
Section: Climate Changementioning
confidence: 87%
“…This experiment revealed that deliberation did not increase political polarization (i.e., disagreement between Democrats and Republicans, Bago et al, 2020; for further evidence indicating that deliberation manipulations do not increase motivated reasoning, see Strömbäck et al, 2021). Instead, deliberation increased overall accuracy (i.e., agreement with pro-climate change arguments) (Bago et al, 2020b).…”
Section: Climate Changementioning
confidence: 87%
“…Previous studies have argued that the effect of politically motivated reasoning is exacerbated by cognitive sophistication and numeric ability, as people with high reasoning capacity will use that capacity selectively to process information in a manner that protects their own valued beliefs. 27 A recent preregistered replication did, however, fail to find evidence in support of this pattern. 43 Moreover, engagement in conspiracy theories has also been linked to motivated reasoning.…”
Section: Methodsmentioning
confidence: 95%
“…19 The cognitive route to motivated reasoning can broadly be conceptualized as either motivated reasoning as analysis or motivated reasoning as feeling. 26,27 Motivated reasoning as analysis refers to the idea that identity-protective cognition is primarily driven by analytical, system 2 processing, in which people with a high cognitive ability are better equipped to reason their way around information that threatens valued beliefs. On the contrary, motivated reasoning as feelings refers to the idea that identity-protective cognition is primarily driven by intuitive, system 1 processing, in which people base their assessment of information on emotional cues to feel good.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been argued that young children could benefit from motivated cognition because it maintains their motivation while learning despite initial failures (Habicht et al, 2021). This adaptive function of motivated cognition might also explain why some studies have found that higher cognitive abilities go along with a higher, not lower, propensity to display biased belief updating (Da Silva et al, 2019;Kahan, 2012;Kahan et al, 2012;Knobloch-Westerwick et al, 2020;Saunders, 2017;Strömbäck et al, 2021;Szebeni et al, 2021). However, others who tested this link between cognitive abilities and motivated cognition found no evidence of this relationship (Fischer et al, 2022;Pennycook, 2022;Pennycook & Rand, 2019).…”
Section: Cognitive Abilitiesmentioning
confidence: 99%
“…Motivated cognition may be influenced by a variety of individual and situational factors or an interaction thereof. For example, characteristics of the situation may interact with prior beliefs and influence processing ( Caddick & Feist, 2021 ; Enke et al, 2021 ; Golman & Loewenstein, 2018 ; Jain & Maheswaran, 2000 ; Kahan et al, 2012 ; Strömbäck et al, 2021 ). The resulting motivated beliefs then feed into decision-making, but might trigger subsequent distorted information search, adding to the cognitive processes.…”
Section: Processes Of Motivated Cognition In the Context Of Cooperationmentioning
confidence: 99%